Предмет: Математика,
автор: Klaushero
-4х^2+9х-1=(х+1)^2
Помогите пожалуйста
Ответы
Автор ответа:
0
-4x^2+9x-1=(x+1)^2
-4x^2+9x-1=x^2+2x+1
-4x^2+9x-1-x^2-2x-1=0
-5x^2+7x-2=0 *-1
5x^2-7x+2=0
a=5 b=-7 c=2
d=b^2-4ac=49-40=9
x1,2= -b+-корень d разделить на 2a=7+-3 разделить на 10
x1=1
x2=0,4
-4x^2+9x-1=x^2+2x+1
-4x^2+9x-1-x^2-2x-1=0
-5x^2+7x-2=0 *-1
5x^2-7x+2=0
a=5 b=-7 c=2
d=b^2-4ac=49-40=9
x1,2= -b+-корень d разделить на 2a=7+-3 разделить на 10
x1=1
x2=0,4
Похожие вопросы
Предмет: Английский язык,
автор: vvvvs0nqx
Предмет: Русский язык,
автор: Ushebaru
Предмет: Математика,
автор: lenamalikovskij
Предмет: Математика,
автор: рлпгдмрг